Fiber Optic-Based Refractive Index Sensing at INESC Porto - Orlando Frazão; José L. Santos; Gaspar Rego; José M. Baptista; Diana Viegas; Paulo Caldas; Luis Coelho; Paula Tafulo; Susana O. Silva; Carlos Gouveia; Pedro A. S. Jorge (Sensors, 2012)
A review of refractive index measurement based on different types of optical fiber sensor configurations and techniques is presented. It addresses the main developments in the area, with particular focus on results obtained at INESC Porto, Portugal. The optical fiber sensing structures studied include those based on Bragg and long period gratings, on micro-interferometers, on plasmonic effects in fibers and on multimode interference in a large spectrum of standard and microstructured optical fibers.